A pharmacological challenge predicts reversible rectal sensorimotor dysfunctions in women with fecal incontinence. Issue 10 (1st June 2018) - Sharma, M.; Feuerhak, K.; Zinsmeister, A. R.; Bharucha, A. E.
Abstract: Background: In order to understand the pathophysiology of rectal sensorimotor dysfunctions in women with fecal incontinence (FI) and rectal urgency, we evaluated the effects of a muscarinic antagonist and an adrenergic α2 agonist on these parameters. Methods: Firstly, rectal distensibility and sensation were evaluated with a barostat and sinusoidal oscillation at baseline and after randomization to intravenous saline or atropine in 16 healthy controls and 44 FI patients. Thereafter, FI patients were randomized to placebo or clonidine for 4 wk; rectal compliance and sensation were revaluated thereafter. The effect of atropine and clonidine on rectal functions and the relationship between them were evaluated. Results: At baseline, compared to controls, rectal capacity was lower ( P = .03) while the mean pressure ( P = .02) and elastance ( P = .01) during sinusoidal oscillation were greater, signifying reduced distensibility, in FI. Compared to placebo, atropine increased ( P ≤ .02) the heart rate in controls and FI and reduced ( P = .03) the variability in rectal pressures during sinusoidal oscillation in controls. Clonidine increased rectal compliance ( P = .04) and reduced rectal capacity ( P = .03) in FI. The effects of atropine and clonidine on compliance ( r = .44, P = .003), capacity ( r = .34, P = .02), pressures during sinusoidal oscillation ( r = .3, P = .057), pressure ( r = .6, P < .0001), and volume sensory thresholds ( r = .48, P = .003) were correlated. Conclusions: The effects of atropine and clonidine on rectal distensibility and sensation were significantly correlated. A preserved response to atropine suggests that reduced rectal distensibility is partly reversible, mediated by cholinergic mechanisms, and may predict the response to clonidine, providing a pharmacological challenge. Abstract : Women with urge FI have reduced rectal distensibility and increased sensation. Overall, atropine and clonidine had minimal effects on rectal capacity and compliance. However, the effects of atropine and clonidine on rectal distensibility and sensation were significantly correlated.